The `repricing’ of executive stock options - Chance, Don M; Kumar, Raman; Todd, Rebecca B (Journal of Financial Economics, 2000)
We examine a sample of firms that reset the exercise prices on their executive options. These repricings follow a period of about one year of poor firm-specific performance in which the average firm loses one-fourth of its value. No other offsetting changes to option terms or compensation are made, and many firms reprice more than once. Without repricing, a majority of the options would have been at-the-money within two years. We find that when faced with circumstances in which repricing might be chosen, firms with greater agency problems, smaller size, and insider- dominated boards are more likely to reprice.